Temporal changes in the composition of a large multicenter kidney exchange clearinghouse: Do the hard‐to‐match accumulate?. Issue 11 (12th September 2018) - Holscher, Courtenay M.; Jackson, Kyle; Thomas, Alvin G.; Haugen, Christine E.; DiBrito, Sandra R.; Covarrubias, Karina; Gentry, Sommer E.; Ronin, Matthew; Waterman, Amy D.; Massie, Allan B.; Garonzik Wang, Jacqueline; Segev, Dorry L.
Abstract : One criticism of kidney paired donation (KPD) is that easy‐to‐match candidates leave the registry quickly, thus concentrating the pool with hard‐to‐match sensitized and blood type O candidates. We studied candidate/donor pairs who registered with the National Kidney Registry (NKR), the largest US KPD clearinghouse, from January 2012‐June 2016. There were no changes in age, gender, BMI, race, ABO blood type, or panel‐reactive antibody (PRA) of newly registering candidates over time, with consistent registration of hard‐to‐match candidates (59% type O and 38% PRA ≥97%). However, there was no accumulation of type O candidates over time, presumably due to increasing numbers of nondirected type O donors. Although there was an initial accumulation of candidates with PRA ≥97% (from 33% of the pool in 2012% to 43% in 2014, P = .03), the proportion decreased to 17% by June 2016 ( P < .001). Some of this is explained by an increase in the proportion of candidates with PRA ≥97% who underwent a deceased donor kidney transplantation (DDKT) after the implementation of the Kidney Allocation System (KAS), from 8% of 2012 registrants to 17% of 2015 registrants ( P = .02). In this large KPD clearinghouse, increasing participation of nondirected donors and the KAS have lessened the accumulation of hard‐to‐match candidates, but highly sensitized candidates remain hard‐to‐match. Abstract : In a large kidney paired donation clearinghouse following an initial accumulation of candidates with panel‐reactive antibody 97% and higher, the Kidney Allocation System mitigated further accumulation of highly sensitized candidates while the increase in nondirected donors over time, who were more likely to have blood type O, mitigated accumulation of candidates with blood type O.